2012
DOI: 10.1271/bbb.111002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Tyrosinase Inhibitory Activity of Mori Cortex Radicis Extract by Biotransformation UsingLeuconostoc paramesenteroidesPR

Abstract: Mori Cortex Radicis (MCR), the root bark of Morus alba L., consists of various phytochemicals and exhibits a strong inhibitory effect on tyrosinase. To enhance the tyrosinase inhibitory activity of MCR extract without further purification of bioactive compounds, whole MCR extract was biotransformed with crude enzyme extract from a selected lactic acid bacterium, Leuconostoc paramesenteroides PR (LP). Mulberroside A (MA), a major stilbene glucoside of MCR, contains two β-glucosyl residues at the C3 and C4' posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…4b ). Kim et al [ 54 ] reported that ethanolic extract of Cortex radicis bio-transformed by Leuconostoc paramesenteroides PR effectively enhanced the tyrosinase inhibitory activity by 6.5-fold in in vitro . Also Usuki et al [ 55 ] demonstrated that LAB and/or their derivatives have wide range of application in the development of skin-whitening and cosmetic products with antioxidant potential that could directly inhibit tyrosinase enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…4b ). Kim et al [ 54 ] reported that ethanolic extract of Cortex radicis bio-transformed by Leuconostoc paramesenteroides PR effectively enhanced the tyrosinase inhibitory activity by 6.5-fold in in vitro . Also Usuki et al [ 55 ] demonstrated that LAB and/or their derivatives have wide range of application in the development of skin-whitening and cosmetic products with antioxidant potential that could directly inhibit tyrosinase enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…The first study describes the use of cellulase to catalyze the deglycosylation reaction of ORV glucosides in a Veratrum patulum extract [ 138 ]. ORV could also be produced from mulberroside A in a Morus alba root extract through a hydrolytic reaction catalyzed by the enzyme Pectinex [ 139 , 140 ], as well as by the enzyme extract obtained from the acid bacterium Leuconostoc paramesenteroides [ 141 ].…”
Section: Productionmentioning
confidence: 99%
“…Inhibition of tyrosinase and related activities by ORV (1) 34,37,49,61,63,67,77,84,97,109,111,124,128,138,139,141,[148][149][150][151][152][153][154][155]. …”
mentioning
confidence: 99%
“…There are different types of indigenous lactic acid bacteria (LAB) present in nature, and aquatic animals hold a plethora of potential LAB with probiotic properties (Balcazar et al, 2008). Currently, LAB are used as probiotics adhering number of beneficial properties such as antibacterial activity (Rather et al, 2013), antifungal activity (Rather et al, 2014), immune modulation (Kamiya et al, 2017, Kim et al, 2012, Kober and Bowe, 2015, Tsai et al, 2010), anti-obesity (Tsai et al, 2014), and anti-diabetic properties (Bajpai et al, 2016) and so on. Due to the production of metabolic characteristics, LAB are considered as novel bacteria for their applications in food and pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%